Adjustment factors and firms’ rational financing behaviour. Malaysia evidence - Haron, Razali (2013)

(untitled)
This study examines the capital structure practice of 790 Malaysian firms from 2000 until 2009. Using a dynamic framework results show that firms in Malaysia do practice target capital structure and take into account certain firm characteristics in their capital structure decisions. The firms appear to readjust instantaneously when they are off the target indicating low adjustment cost and smaller firms adjust more quickly than their larger counterparts. The use of internal funding implies the influence of the pecking order hypothesis in deciding the readjustment process. Most firms in Malaysia are found to be overly in debt or over-levered due to the good economic growth during the period understudy and are said to behave rationally by cutting down the amount of debt in their capital structure to reach the target. In term of the proximity to target, under-levered firms are found to be much closer to target comparative to the over-levered firms. The optimality ratio of the under-levered firms which corresponds to the fast adjustment speed indicates that the beneﬁts of reaching the target outweigh the adjustment costs. This study contributes to the literature by filling the gap of capital structure studies based on the dynamic model and most importantly by identifying the rational financing behaviour of Malaysian firms. This indication of firms’ proximity to target can help managers to outline and set the next steps to be taken in order to reach the target capital structure to maximise firm value.